FRI0393 Maternal and fetal outcomes in systemic lupus erythematosus. (12th June 2018) - Yii, I.Y.; Yang, L.; Tan, H.K.; Tan, L.K.; Thumboo, J.; Poh, Y.J.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is associated with an increased risk of adverse pregnancy outcomes. Objectives: We aim to evaluate the maternal and fetal outcomes in SLE pregnancies in a single tertiary referral centre. Methods: We retrospectively analysed 75 pregnancies in 45 patients with SLE over a 16 year period from 2000 to 2016. All patients fulfilled the 1997 American College of Rheumatology (ACR) criteria or the Systemic Lupus International Collaborating Clinics (SLICC) criteria for diagnosis of SLE. Results: In our multi-ethnic cohort, there were 65% Chinese, 23% Malays and 7% Indians. The mean age was 32 years old and majority (55%) were nulliparous. The mean SLE disease duration was 5.9 years. Baseline SLE manifestations were predominantly haematological (73%), arthritis (71%) and renal (57%). There were 33 pregnancies (44%) with anti-Ro (SS-A) antibody positivity. There were 9 pregnancies (12%) with SLE and antiphospholipid syndrome. In our cohort, the majority of the patients were on prednisolone (76%). Half of the patients (48%) were on hydroxychloroquine or chloroquine and 27% were on azathioprine. In the subgroup of patients with SLE and antiphospholipid syndrome, 67% (6/9 pregnancies) were treated with therapeutic clexane and 33% (3 pregnancies) with the combination of prophylactic clexane and aspirin. The mean SELENA-SLEDAI score at the booking visit was 4.0. In our cohort, the live birth rate was 75%. More than half of the deliveries were via Caesarean section (57%). There were maternal and fetal complications in 61% of the pregnancies. Pregnancy losses occurred in 16 pregnancies with the majority (87%) being early pregnancy losses that occurred prior to 13 weeks gestation. There were 13 pregnancies (17%) with intrauterine growth restriction and 18 pregnancies (24%) with preterm delivery. In the subgroup of the preterm births, 2 were extremely preterm birth (<28 weeks gestation) and 2 were very preterm birth (28 weeks to <32 weeks gestation). There were no cases of congenital heart block or neonatal lupus. There was one neonatal death. SLE flares occurred in 25 pregnancies (33%). The most common organ involvement were haematological (44%), renal (40%), mucocutaneous (28%) and arthritis (16%) Pre-eclampsia occurred in 2 pregnancies (2%). There were 3 cases of a first presentation of lupus nephritis in pregnancy. In the subgroup of SLE pregnancies with antiphospholipid syndrome, there were higher SLE flare rates (44%) and more adverse pregnancy outcomes with 3 pregnancies (33%) that resulted in miscarriages, 2 pregnancies (22%) with preterm delivery and one pregnancy (11%) complicated by pre-eclampsia (table 1). There were 7% of pregnancies with a post-partum SLE flare. Conclusions: In our multi-ethnic cohort, more than half of the patients experienced an adverse pregnancy outcome. SLE flares in pregnancy occurred in a third of the cohort with the most common organ manifestation being haematological and renal flares. SLE pregnancies with antiphospholipid syndrome appeared to be associated with a higher risk of SLE flares and adverse pregnancy outcomes. Disclosure of Interest: None declared